2019
DOI: 10.1039/c9dt04288a
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating ethylene polymerization using secondary metal ions in tetrahydrofuran

Abstract: A variety of metal cations are capable of enhancing the ethylene polymerization rates of nickel phosphine phosphonate-polyethylene glycol catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 64 publications
0
26
0
1
Order By: Relevance
“…The standard catalyst Ni1 was prepared according to our previously published procedures . To rigidify the PO side of the nickel complex, we synthesized two new ligand derivatives 6a (R = methoxy) and 6b (R = 2-methoxyethoxy) (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The standard catalyst Ni1 was prepared according to our previously published procedures . To rigidify the PO side of the nickel complex, we synthesized two new ligand derivatives 6a (R = methoxy) and 6b (R = 2-methoxyethoxy) (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Both Ni2 and Ni3 adopt pseudo-square planar geometries, similar to that in Ni1 . To determine the steric effects of having different ancillary groups, we compared the structural parameters among Ni1 , Ni2 , and Ni3 (Table ). Although their Ni–P, Ni–O, and Ni–C′ bond distances varied slightly from one another (averages of ∼2.19, 1.90, and 1.98 Å, respectively), they differed at most up to ∼0.03 Å.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Xiao et al [27] have reported that nickel complexes with phosphine phosphonate-PEG ligand in combination with Co 2 + and Zn 2 + cations can enhance the rate of polymerization. This finding agrees with our results.…”
Section: Potent Ni-peg Catalysts With M 2 + Cationmentioning
confidence: 99%
“…Nozaki课题组 [79] 设计的具有类似结构的膦酚镍催化剂可以进行丙烯与不同类型的极性单体共聚,但 该体系共聚活性比较低(最高只能达到10 4 g mol -1 h -1 ) 、极性单体插入比较低(最高达到2.4 mol%) 组 [92] 报道了六元环膦-膦氧镍催化剂F8-1,其可以催化乙烯和10-十一烯酸甲酯和长链氯的共聚合。 Do课题组 [93] 发展了一类带有多氧边臂的膦-膦氧镍催化体系F8-2,侧臂的氧原子可以和不同类型的 路易斯酸金属离子配位。特定离子配位后的镍催化剂在催化乙烯和极性单体共聚时,其活性、共聚 物分子量以及插入比均有明显的提高。2019年,本课题组 [94] 首次报道了一类新型五元环膦-膦氧镍…”
unclassified